Engagement and flexibility: An empirical discussion about consultative leadership intent for productivity from Pakistan - Dian Ekowati; Ansar Abbas; Aisha Anwar; Fendy Suhariadi; Mochammad Fahlevi (Cogent Business & Management, 2023)
Change and development are continuous processes inside organizations. Maintaining a high level of productivity is critical at all times. Flexibility and engagement are the two most essential factors in determining productivity. Leadership is necessary for an organization to manage these characteristics to be produced correctly. Nevertheless, consultative leadership has been determined to be the most theoretically appropriate form of leadership. The model has been tried and tested in Pakistani higher educational settings. The findings of this study provide evidence that the proposed model is booming, and the pertinent parts of this paper clarify the theoretical and practical aspects of the model.
Keywords: 650; Consultative leadership; education; engagement; flexibility; positive leadership; productivity; strategic intent